Pre-Lessepsian isotopic niche spaces: using paleoecological proxies to assess the impact of ongoing bioinvasions on fishes in the eastern Mediterranean Sea - WINTER, RACHEL M.; DESIDERÁ, ELENA; GUIDETTI, PAOLO; VON TERSCH, MATTHEW; DEE, MICHAEL; ALEXANDER, MICHELLE; ÇAKIRLAR, CANAN (Mediterranean Marine Science, 2025)
Ongoing bioinvasions of Lessepsian species via the Suez Canal have profoundly altered marine coastal ecosystems in the eastern Mediterranean. In response to these Lessepsian migrations, some indigenous fishes have been observed to have widened their trophic niches and diversified their foraging strategies. Effects of invasive taxa are further compounded by modern anthropogenic drivers such as overfishing, habitat degradation, and pollution. The scale and characteristics of these recent changes in trophodynamics for broader ichthyofaunal communities are poorly understood due to a lack of data predating Lessepsian migrations; paleoecological data is, therefore, essential. Here, we present a substantial body of new carbon (δ13C) and nitrogen (δ15N) isotopic data from Middle to Late Holocene archaeological fish collagen (n=137), combined with previously published results (n=44) to establish paleoecological baselines for the region. An emphasis is placed on groupers (Epinephelidae) due to their high ubiquity in Mediterranean archaeological contexts and importance to rocky reef ecosystems today. We demonstrate that modern, indigenous Mediterranean fish have expanded their trophic niches beyond their pre Lessepsian migrations baseline foraging ecology. Paleo data further show that fishes in middle and lower trophic levels have the highest degree of overlap in isotopic niche spaces, suggesting greater levels of competition for trophic resources. Our study highlights the importance of integrating data from historical ecological baselines into our assessments of bioinvasions and, more broadly, anthropogenically driven ecosystem alterations.